Gregory of Tours, Solomon’s Temple, and the Seven Wonders: Splendor and Ephemerality - Deliyannis, Deborah Mauskopf (Vigiliae Christianae, 2025)
Gregory of Tours begins De cursu stellarum ratio with a list of the Seven Wonders of the World, contrasting their impermanence with the natural wonders of God’s creation. Gregory’s list of the Seven Wonders is innovative, because it includes the Temple of Solomon, an idea that he got from a poem by Sidonius Apollinaris. The Seven Wonders, known in classical literature since the 2nd century BC, represent great feats of human ingenuity; Gregory’s inclusion of the Temple of Solomon demonstrates that it was even more splendid than pagan Wonders. However, some classical authors had used the Wonders to emphasize the ephemerality of man-made structures, and ascetic Christian authors argued the same thing about the Temple of Jerusalem. Gregory’s inclusion of the Temple of Solomon fuses these traditions, producing a powerful Christian statement both about the splendid Temple commanded by God, and about the ultimate ephemerality of human-made splendor.